Effects of COVID-19-related stay-at-home order on neuropsychophysiological response to urban spaces: Beneficial role of exposure to nature?. (June 2021) - Olszewska-Guizzo, Agnieszka; Fogel, Anna; Escoffier, Nicolas; Ho, Roger
Abstract: Background: The COVID-19 pandemic has had severe negative effects on populations worldwide. The seriousness of the pandemic necessitated local and even national lockdowns. In Singapore a national lockdown with aStay-at-Home Order (SHO) lasted for over 7 weeks. The impact of the pandemic and of the long SHO period on neuropsychophysiological functioning remains unknown. Studies prior to the pandemic highlighted the beneficial role of nature exposure on mental health and well-being, although this has not yet been explored in the post-pandemic world. This is the first study to investigate the longitudinal changes in (1) brain frontal alpha asymmetry (FAA; neuroelectric marker of approach-related motivation), (2) depressive mood and (3) symptoms, and (4) emotional response to videos of various urban spaces from before COVID-19 to immediately after the SHO in Singapore was over. Finally, we examined whether higher vs lower exposure to nature during the SHO moderated changes over time. Methods: The sample included 25 healthy adult Singaporeans (56% female, Mage  = 40.4 y, SD = 17.8), who attended two electroencephalography (EEG) lab sessions, within a year before the COVID-19 pandemic (T1) and immediately following the SHO (T2). The participants viewed 9 fixed-frame videos, filmed before the pandemic, from 3 urban public spaces (Busy Downtown, Residential Green, Lush Garden) on the roll-up screen. They rated their emotional response (arousal, valence) after each video and completed Becks Depression Inventory-II (BDI-II) as a measure of depressive symptoms, Profile of Mood Scale (POMS), as a measure of momentary mood, and self-reported the frequency and duration of their nature visits during the SHO. Results: Linear mixed models were fitted to examine changes over time, and effect moderation by amount of nature exposure during the SHO. The results showed decrease in FAA (p < 0.001), increase in depressive symptoms (p = 0.046), and a trend for marginal increase in momentary mood disturbance (p = 0.097) after the SHO. Importantly, people with high nature exposure during SHO had greater decrease in FAA over time (p = 0.005) than those with low nature exposure, FAA scores decreased the most for Residential Green. Valence and Arousal did not change over time, but Arousal towards Busy Downtown decreased among high nature exposure individuals (p = 0.002). Conclusions: Post SHO, brain activity and responsiveness to landscapes changed, and showed a general reduction in positive emotions and increased depressive symptoms among participants. The higher nature exposure during the SHO did not help mitigate this depressive symptoms, as previous research would suggest. This can be due to the modified quality of nature exposure during lockdown, which highlights the importance of high quality nature experience in cities and the provision of diversified visual exposures. Potential neuropsychophysiological consequences of SHO should be considered by policy makers in the post-COVID-19 world. Highlights: First within-subjects study on the neurophysiological response to urban spaces before and after the COVID-19 lockdown. Data collected at highly urbanized city of Singapore. Significant increase in depressive symptoms after the lockdown, effect observed in the brain scans greater than self-reports. Nature exposure during the lockdown did not moderate the levels of depression post lockdown. Diversity of urban landscape exposure and high quality of green urban space can be a key to mentally healthier cities.